Analisis Pengaruh Biaya Produksi terhadap Laba Bersih pada PT. Aneka Tambang Tbk - Zainuddin, Elza; Wahab, Abdul; Masse, Rahman Ambo (Institut Agama Islam Negeri Parepare, 2023)
Profit is a part that is always a target to be achieved by a company. every company. To obtain maximum profit, the company must be able to reduce production costs incurred in its operations. This study aims to determine the effect of production costs on net profit at PT. Aneka Tambang Tbk. This study uses a quantitative approach. The data used is secondary data obtained from the quarterly financial reports of PT. Aneka Tambang Tbk. starting from 2018 to 2021 which is adjusted to the financial reports on the Indonesian Stock Exchange. The analysis used in this research is simple linear regression analysis. The results showed that the production cost variable had a significant positive effect on net income. This significant positive result is evidenced by the results of the Production Cost t-test which has a significance value of 0.006 in the positive direction. The level of strength of the relationship between production costs and net profit is in the medium category because the coefficient of determination obtained is 42.6%.